Leadership in the promotion of peace: Interviews with the 2015 Business for Peace honorees - Katsos, John (2016)
Ethical leadership can lead to many positive organizational outcomes. Previous studies have shown a correlation between ethical conduct and profitability; in addition, firms that have high ethical standards have fewer legal issues. The existing ethical leadership literature assumes a stable external environment. The business and peace literature, on the other hand, assumes instability but has thus far largely ignored the role of leadership within companies as a possible driver of peacebuilding activities. The practitioner community has already begun to recognize that leaders of organizations are the key drivers of change in the peacebuilding context. The Business for Peace Foundation, the foremost organization in the practitioner community, gives its annual award to business leaders who promote peace within their organizations and communities. These Business for Peace honorees represent the ‘ethical leadership’ qualities of peace promotion, without reference to academic theories in either area. We conducted semi-structured interviews with the 2015 Business for Peace honorees and combined those with their public speeches at the Business for Peace events to examine what role these business and peace leaders saw between ethical leadership and peace promotion. Unlike the academic research that suggests only a theoretical and sometimes a direct but tangential connection to peacebuilding, the honorees highlight the direct and visible connection of ethical leadership to peace in unstable environments. We begin by describing the relevant business for peace and ethical leadership literatures. Then we highlight the significant aspects of the interviews and speeches and relate these to the prevailing theories of both business and peace and ethical leadership. Our findings suggest that ethical leadership may be an important missing link within the business and peace literature as an avenue for peace promotion, and that the leadership literature may be ignoring an important positive impact of ethical leadership.